Counselling of Parents, attendants, guardians in dealing of Paediatic Surgical Patients - Rahman, Kazi Habibur (Journal of Paediatric Surgeons of Bangladesh, 2016)
Abstract not available J. Paediatr. Surg. Bangladesh 6(2): 32, 2015 (July)